ANALISIS HUKUM PERALIHAN HAK ATAS TANAH BERSETIFIKAT HAK MILIK DENGAN SURAT DIBAWAH TANGAN (STUDI PUTUSAN NOMOR 30/PDT.G/2020/PN NABIRE) - Syarif Hidayatullah Pulungan; Muhammad Yamin, Rosnidar Sembiring, Yefrizawati (JOURNAL OF LAW AND NATION, 2023)
Transfer of land rights is the transfer of land rights from the old right holder to the new right holder according to the provisions of the applicable laws and regulations. There are 2 (two) ways of transferring land rights, namely transfer and transfer. The transfer of rights to land that has been certified as ownership should be carried out by means of a legal act of sale and purchase carried out before a public official, namely the PPAT, which has the authority to make authentic deeds regarding land rights or ownership rights to apartment units. The transfer of land rights that have been certified as ownership through an agreement with a private letter still has legal force and can be used as evidence in court. However, it is not as strong and complete as an authentic deed made before a public official. This research method uses a Normative Juridical research type which is descriptive analytical in nature. The data source uses secondary data sources using legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials using library research data collection techniques (Library Research) and the data collection tool in this research is document study. The results of the research show that the transfer of title to land with certificate of ownership with a private letter still has valid legal force, based on the laws in force in Indonesia. Regarding land matters, there are 3 (three) forms of law that can be used as guidelines, namely the Basic Agrarian Law (UUPA), the Civil Code (KUHPerdata) and Customary Law. The transfer of land rights based on customary law is considered valid if it does not conflict with applicable laws and regulations according to the legal hierarchy. Legal protection for legal subjects who carry out legal acts of transferring title to certified land with private documents will be guaranteed and protected by the state as long as it can be proven in the judicial process. The essence of this case is that there was an unlawful act committed by one of the parties as the seller which resulted in an error which violated the statutory regulations, there was a loss experienced by the other party as the buyer of the plot of land so that the buyer was unable to carry out the process of changing the name of the a quo land. the. The legal basis is that there is an unlawful act against the conditions for the validity of an agreement written in article 1320 of the Civil Code.